1996
DOI: 10.1016/0376-7388(95)00125-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-aqueous retention measurements: ultrafiltration behaviour of polystyrene solutions and colloidal silver particles

Abstract: The retention behaviour of polyimide ultrafiltration membranes was investigated using dilute solutions of polystyrene in ethyl acetate as test solutions. It is shown that flow-induced deformation of the polystyrene chains highly affects the membrane retention. This coil-stretch transition is not instantaneous, but gradual. The concept of a deformation resistance has been introduced to explain this behaviour. This concept can be applied to describe the flux behaviour of the membranes during the tests as well. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2000
2000
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
4
21
0
Order By: Relevance
“…4B. Such an experiment may explain why most of previously observed ultrafiltration transitions [24,31,34,35] were smooth, instead of sharp. In contrast, a continuously 3-dimentional networklike membrane is highly not recommended for the quantitative ultrafiltration-related study because of its poorly defined pore geometry.…”
Section: Translocation Of a Linear Chain: Effect Of The Chain Length mentioning
confidence: 77%
See 3 more Smart Citations
“…4B. Such an experiment may explain why most of previously observed ultrafiltration transitions [24,31,34,35] were smooth, instead of sharp. In contrast, a continuously 3-dimentional networklike membrane is highly not recommended for the quantitative ultrafiltration-related study because of its poorly defined pore geometry.…”
Section: Translocation Of a Linear Chain: Effect Of The Chain Length mentioning
confidence: 77%
“…However, most of studies [24,31,33,34] reported a smooth transition from total retention to forced penetration, except for us [26,28]. Namely, Beerlage et al [31] investigated the retention behavior of linear polystyrenes in ethyl acetate. It was shown that the "coil-stretch" transition is not precipitous, but gradual; and the critical volumetric flow rate is chain length and polymer concentration independent in dilute solution.…”
Section: Translocation Of a Linear Chain: Effect Of The Chain Length mentioning
confidence: 97%
See 2 more Smart Citations
“…There have been numerous studies (de Rooy et al, 1980;Kandori et al, 1984;Kosmulski and Matijevic, 1992;Kage et al, 1993;Ketelson et al, 1996;Chadwick et al, 2002) on the colloidal stability and electrokinetic properties of dispersions in the aqueous organic solvent. However, related filtration study is rather scarce (Gupta et al, 1995;Lencki and Williams, 1995;Beerlage et al, 1996) since, until now, most studies have been done with aqueous colloidal suspensions, thus little understanding currently exists regarding the effect of aqueous organic solvents on filtration behavior of colloidal solutions.…”
Section: Introductionmentioning
confidence: 99%